Learning preferences of medical students - a study conducted at the University of Peradeniya, Sri Lanka - D. Edussuriya; S. Ubhayasiri; N. Abeysiriwardhana; M. Wickramasinghe (Sri Lanka Journal of Medicine, 2016)
Background: Each student has a unique way of learning. These preferred learning approaches are believed to have an influence on student learning and academic performance. Identifying the learning preference of students is important as it would inform the teachers of the most suitable way of engaging students. Objectives: To determine the learning preference of medical undergraduates of the University of Peradeniya, Sri Lanka and to identify whether there is a significant difference in the learning preference based on gender, academic seniority and academic performance. Methods: Six hundred medical undergraduates of the University of Peradeniya, Sri Lanka were assessed using paper copies of the VARK questionnaire. Data were analysed using SPSS. Results: The response rate was 94%. The number of multi-modal learners (56.6%) was significantly higher than uni-modal learners (43.4%). All multi-modal learners were quad-modal learners and a majority had a high preference for VARK type 1 (switching from mode to mode depending on the context) learning style (35.4%). A significant proportion of uni-modal learners had a visual preference (28.9%) with few having auditory, read/write and kinaesthetic preferences. There was no significant difference between males and females in their learning preference. There was a trend towards becoming more multi-modal as they progress to senior years. A majority of second upper class achievers (61.5%), second lower class achievers (50.9%) and passed students (65.9%) showed a multi-modal learning preference. However, there was no significant difference in preference for uni-modal or multi-modal learning among first class holders.